Brain Arteriovenous Malformations associated with Hereditary Hemorrhagic Telangiectasia: Gene-Phenotype Correlations - Nishida, Takeo (2012)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant genetic disease with a wide spectrum of vascular malformations involving multiple organs. Nine-16% of patients with HHT harbor brain arteriovenous malformations (AVMs), which can cause intracranial hemorrhage. Our objective was to study clinical manifestations of brain AVM in patients with HHT and correlate these with the specific gene mutated. We reviewed records of 171 patients with HHT and brain AVMs. A history of intracranial hemorrhage was found in 27% (41/152) patients, with a mean (range) age of 26 +/− 18 (0–68) years. All patients with intracranial hemorrhage were neurologically asymptomatic prior to intracranial hemorrhage. Multiple brain AVMs were found in 23% (170/39) of patients on initial examination. Genetic test results were available in 109 (64%) patients. Mutations in ENG, ACVRL1, and SMAD4 were present in 75 (69%), 18 (17%) and 2 (2%), respectively. A history of intracranial hemorrhage was reported in 24% of patients with an ENG mutation and 27% of patients with an ACVRL1 mutation, with a mean (range) age of 26 +/− 16 (2–50) and 18 +/− 21 (0–48) years, respectively. No statistically significant differences in age at first brain AVM diagnosis, prevalence of intracranial hemorrhage history, age at intracranial hemorrhage, or other manifestations of brain AVMs were observed among gene groups. In conclusion, no evidence for differences in brain AVM characteristics was observed among HHT gene groups, although we cannot exclude clinically important differences. Larger studies are needed to further guide brain AVM screening decisions in patients with HHT.